Opportunities and limits to market-driven sanitation services: evidence from urban informal settlements in East Africa. (October 2015) - O'Keefe, Mark; Lüthi, Christoph; Tumwebaze, Innocent Kamara; Tobias, Robert
The improvement of sanitation conditions in slums (1) is difficult in part because of economic and institutional environments that often prevent private or public investment in infrastructure. This analysis of sanitation conditions in informal settlements in Nairobi and Kampala compares user practices. It also identifies the main actors involved in the provision of overlapping sanitation systems, involving a multitude of small-scale providers, along with the challenges these present. The paper goes on to describe a new market-based approach in Nairobi, developed by a social enterprise, Sanergy, which is responsible for the construction of facilities and the collection and treatment of wastes. The system improves user satisfaction, community wellbeing and environmental quality, pointing to a clear opportunity for such market-based interventions where a customer base already pays for sub-standard services. There remain challenges, however, around the ability to scale up and finance these providers, especially in complex operating environments that increase transactional costs for companies.